1996
DOI: 10.20870/oeno-one.1996.30.3.1103
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative study of interaction between <em>Saccharomyces cerevisiae</em> and <em>Leuconostoc oenos</em>

Abstract: <p style="text-align: justify;">Weak malolactic fermentations in wine making are often attributed to the medium constituents such as ethanol and SO<sub>2</sub>. However, some authors report that the interactions between <em><em>Saccharomyces cerevisiae</em></em> and <em>Leuconostoc oenos</em> could be responsible too.</p><p style="text-align: justify;">The aim of this work is to characterize the influence of <em>S. cerevisiae</em> on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Our previous studies indicated that yeast strains used in this work are poor fatty acid producers. Another possible explanation for inhibition of LAB growth proposed by certain authors is the depletion of nutrients by wine yeasts during AF (Gilis, Dupuy, & Strehaiano, 1996;Nygaard & Prahl, 1997). However, in the present work, prior to sequential inoculation with LAB, the yeastfermented media were supplemented with MRS components to rule out the lack of nutrients (see Materials and methods).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies indicated that yeast strains used in this work are poor fatty acid producers. Another possible explanation for inhibition of LAB growth proposed by certain authors is the depletion of nutrients by wine yeasts during AF (Gilis, Dupuy, & Strehaiano, 1996;Nygaard & Prahl, 1997). However, in the present work, prior to sequential inoculation with LAB, the yeastfermented media were supplemented with MRS components to rule out the lack of nutrients (see Materials and methods).…”
Section: Discussionmentioning
confidence: 98%
“…Our knowledge of the interactions between yeast and bacteria in the wine environment remains incomplete, and further investigations are required to determine the specific role of yeast with respect to the MLB (Edwards and Beelman, 1987;Lemaresquier, 1987;Gilis et al, 1996;Addis et al, 2001;Arnink et al, 2002). Indeed, previous studies have indicated that many factors can negatively influence the regular development of MLF (Britzh and Tracey, 1990;Radler, 1990;Guerzoni et al, 1995;Reguant et al, 2000;Vidal et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that there are a large number of parameters that can affect correct bacterial growth, and consequently MLF (Capucho and San Romao, 1994;Wibowo et al, 1985;Gilis et al, 1996). In particular, after yeast fermentation, the MLB are in a very harsh environment that is mainly due to the ethanol that is produced, which is the first inhibitory factor of MLB growth (Capucho and San Romao, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the control of MLF in wine has been carried out by using the chemical antiseptic agent SO 2 . More recently, the use of lysozyme and nisine has been proposed to protect wine and other fermented beverages (Ogden 1986; Radler 1990a,b; Gilis et al. 1996) from the activity of spoilage lactic acid bacteria, and the effect of yeast–MLB interactions in wine has started to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the control of MLF in wine has been carried out by using the chemical antiseptic agent SO 2 . More recently, the use of lysozyme and nisine has been proposed to protect wine and other fermented beverages (Ogden 1986;Radler 1990a,b;Gilis et al 1996) from the activity of spoilage lactic acid bacteria, and the effect of yeast-MLB interactions in wine has started to be explored. Indeed, further knowledge of the interactions occurring between wine micro-organisms is required, either for the evaluation of the possibility of controlling undesired MLB activities by means of natural antibacterial agents produced by yeast, or for the avoidance of any negative interactions in all the cases in which MLF has to be promoted.…”
Section: Discussionmentioning
confidence: 99%